The Aesthetics of Encounter: A Relational-Performative Design Approach to Human-Robot Interaction - Gemeinboeck, Petra (Frontiers in Robotics and AI, 2021)
This article lays out the framework for relational-performative aesthetics in human-robot interaction, comprising a theoretical lens and design approach for critical practice-based inquiries into embodied meaning-making in human-robot interaction. I explore the centrality of aesthetics as a practice of embodied meaning-making by drawing on my arts-led, performance-based approach to human-robot encounters, as well as other artistic practices. Understanding social agency and meaning as being enacted through the situated dynamics of the interaction, I bring into focus a process of bodying-thinging, entangling and transforming subjects and objects in the encounter and rendering elastic boundaries in-between. My notion of a relational-performative design approach—designing with bodying-thinging—proposes that we engage with human-robot encounters from the earliest stages of the robot design. This is where we begin to manifest boundaries that shape meaning-making and the potential for emergence, transformation and connections arising from intra-bodily resonances (bodying-thinging). I argue that this relational-performative approach opens up new possibilities for how we design robots and how they socially participate in the encounter.